Top-down attentional factors modulate action priming in reach-to-grasp action. Issue 7 (July 2019) - Sparks, Samuel; Lyons, Maxwell; Kritikos, Ada
Previous studies report that viewing exaggerated, high-lifting reaches (versus direct reaches) primes higher vertical deviation in wrist trajectory in the observer's subsequent reaches (trajectory priming), but it is unclear to what extent this effect depends upon task instructions relevant to top-down attention. In two experiments, participants were instructed to gaze at a dot presented on a large monitor for a colour-change go signal that cued them to execute a direct reach to a target. In the background, the monitor also displayed life-sized films of a human model. The films were of the model either remaining still or reaching to grasp a target with either a direct trajectory or an exaggerated, high-lifting trajectory. When the dot traced the human model's wrist throughout her movement, a robust trajectory priming effect emerged. When the dot remained stationary in a central location but the human model reached in the background, the human model's trajectory did not alter the participants' trajectories. Finally, when the dot traced exaggerated and direct trajectories and the human model remained stationary, the dot's movement produced an attenuated, non-significant trajectory priming effect. These findings show that top-down attentional factors modulate trajectory priming. In addition, a moving non-human stimulus does not produce the same degree of action priming when contextual factors make salient its independence of human agency and/or intention.